Clinical Analysis of Channa micropeltes for Treating Wound of Diabetes Mellitus - Maharani Laillyza Apriasari; Marina Arum Syahadati; Amy Nindia Carabelly (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: Toman fish contains albumin and omega-6 fatty acid that are instrumental in the healing process of diabetes mellitus (DM) wound. People with DM usually have a prolonged wound healing process. Albumin controls the osmotic pressure, the development of granulation tissue, gives the energy to re-epithelialisation process and collagen base material. Omega-6 fatty acid interrupts phagocytosis induced by neutrophil cells. It increases the action of machropage cell, so that Toman fish can be used as an alternative in accelerating the DM wound healing process. The purpose of this research is to prove the effect of Toman fish extract at 16 mL/ KgBW rat dosage per oral on wound length and contraction on the back of wistar rat (Rattus novergiucs) with DM for 14 days. It was the experimental with a posttest only with control group design used 12 wistar rat that were divided into 3 groups; the group of Toman fish extract with dose 16 mL/ Kg BW rat, positive control group using Haruan extract with dose 13,54 mL/ Kg BW rat and negative control group using Comfeed BR2 feed. One-way ANOVA test result for wound length and contraction (p= 0,000). The result Post-hoc Least Significant Difference test for wound length and contraction shows that there are significant differences between the group of Toman fish extract and Haruan fish extract (p= 0,000). There is also significant difference between the group of Toman fish extract and Comfeed BR2 feed (p= 0,000). There is no significant difference between the group of Haruan fish extract and Comfeed BR2 feed (p= 0,930). The research concluded that Toman fish extract at 16 mL/ Kg BW rat dosage affects the length and contraction of diabetic mellitus wound. Keywords: Channa micropeltes, clinical analysis, diabetes mellitus, wound